2020
DOI: 10.3390/pathogens9080640
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma bovis Infections—Occurrence, Diagnosis and Control

Abstract: Mycoplasma bovis is a cause of bronchopneumonia, mastitis and arthritis but may also affect other main organs in cattle such us the eye, ear or brain. Despite its non-zoonotic character, M. bovis infections are responsible for substantial economic health and welfare problems worldwide. M. bovis has spread worldwide, including to countries for a long time considered free of the pathogen. Control of M. bovis infections is hampered by a lack of effective vaccines and treatments due to increasing trends in antimic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 82 publications
(147 reference statements)
2
47
0
1
Order By: Relevance
“…Concerning M. bovis and SCC, earlier studies suggested that infection with M. bovis can elevate SCC in individual and BTM samples [ 28 ]. Therefore, the generally recommended rule to control intramammary infections due to M. bovis is sampling of cows with high SCC in milk [ 29 ]. However, more recent studies in individual milk suggest that due to the finding that not all culture positive animals show higher SCC, if SCC are used as the single basis for a mastitis control program in a farm, they may lead to the omission of M. bovis positive animals.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning M. bovis and SCC, earlier studies suggested that infection with M. bovis can elevate SCC in individual and BTM samples [ 28 ]. Therefore, the generally recommended rule to control intramammary infections due to M. bovis is sampling of cows with high SCC in milk [ 29 ]. However, more recent studies in individual milk suggest that due to the finding that not all culture positive animals show higher SCC, if SCC are used as the single basis for a mastitis control program in a farm, they may lead to the omission of M. bovis positive animals.…”
Section: Discussionmentioning
confidence: 99%
“…Under natural condition, M. bovis interanimal transmission occurs mainly via colostrum, milk, air-borne, intrauterine, and contaminated semen (4). Moreover, M. bovis has the capability to produce a biofilm, making it possible for the bacterium to survive in the environment while withstanding the action of heat or desiccation (5).…”
Section: Introductionmentioning
confidence: 99%
“…M. bovis is the etiological agent of many disorders in cattle with different clinical manifestations, such as pneumonia, mastitis, arthritis, otitis, keratoconjunctivitis, endocarditis and brain disorders [ 3 ]. M. bovis has the ability to form an adherent biofilm, which facilitates its survival in the host and aids the chronic course of the disease [ 1 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%